2017
DOI: 10.21470/1678-9741-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transfusion and Increased Perioperative Risk in Coronary Artery Bypass Grafts

Abstract: ObjectiveTo correlate blood transfusions and clinical outcomes during hospitalization in coronary artery bypass grafting surgery (CABG).MethodsTransfusion, clinical and hematological data were collected for 1,378 patients undergoing isolated or combined CABG between January 2011 and December 2012. The effect of blood transfusions was evaluated through multivariate analysis to predict three co-primary outcomes: composite ischemic events, composite infectious complications and hospital mortality. Because higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In our centre, the decision for blood transfusion was based on the patient’s clinical status (symptomatic anaemia, intra-operative or post-operative excessive/life threatening bleeding, coagulopathies) and/or haemoglobin < 8 g/dL. However, throughout the years, a growing amount of literature has shown that RBC transfusion is associated with morbidity and short-term and long-term mortality after CABG (3335). Although RBC transfusions may certainly have life-preserving value, the impact of smaller quantities of RBCs in a non-emergent setting (i.e., asymptomatic anaemia/bleeding) has not been well documented.…”
Section: Discussionmentioning
confidence: 99%
“…In our centre, the decision for blood transfusion was based on the patient’s clinical status (symptomatic anaemia, intra-operative or post-operative excessive/life threatening bleeding, coagulopathies) and/or haemoglobin < 8 g/dL. However, throughout the years, a growing amount of literature has shown that RBC transfusion is associated with morbidity and short-term and long-term mortality after CABG (3335). Although RBC transfusions may certainly have life-preserving value, the impact of smaller quantities of RBCs in a non-emergent setting (i.e., asymptomatic anaemia/bleeding) has not been well documented.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with increased morbidity and mortality depending on the degree of hemodilution (1-7). Current evidence recommends the reduction of hemodilution and the preservation of Hct for the best outcomes in patients undergoing routine cardiac surgery with CPB (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Hemodilution in cardiac surgery is associated with adverse outcomes that are dependent on the degree of dilution.…”
Section: Discussionmentioning
confidence: 99%
“…RBC transfusion is not without risk. It can lead to immunomodulation, transmission of infectious diseases, allergic reactions, hemolytic reactions, transfusion-related acute lung injury, and increased risk of infection (6,7,9,10,12,13). Furthermore, blood transfusion has been linked to decreased short-term (1, 6, and 12 months) and longterm (5 and 10 years) survival in patients undergoing cardiac surgery (6).…”
Section: -Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 In patients undergoing cardiovascular surgery, moreover, major bleeding and blood transfusion during surgery have been significantly associated with increased early postoperative mortality, even in low-risk patients. 4 In addition, intraoperative hemodynamic instability during and after separation from cardiopulmonary bypass can significantly increase the risk of early postoperative mortality. 5 Thus, not taking intraoperative risk factors into the models might have tampered with the inferences of multivariate logistic regressions adjusted by propensity score for risk factors of early postoperative mortality and their odds ratios.…”
mentioning
confidence: 99%